Information search, integration, and personalization : 10th International Workshop, ISIP 2015, Grand Forks, ND, USA, October 1-2, 2015, Revised selected papers /: 10th International Workshop, ISIP 2015, Grand Forks, ND, USA, October 1-2, 2015, Revised selected papers. (2016) - Unknown
No abstract available